Growth inhibition of the zoonotic bacteria Bacillus anthracis by high antioxidant Australian plants: New leads for the prevention and treatment of anthrax - Cock, I.E.; Wright, Mitchell Henry; Matthews, Ben; Greene, Anthony Carlson (Pharmacognosy Communications)
Introduction: Anthrax is severe acute disease caused by Bacillus anthracis infections. If untreated, it often results in mortality. High antioxidant plant extracts have documented therapeutic properties as general antiseptics, inhibiting the growth of a wide variety of bacterial species. This study examines the ability of selected high antioxidant Australian plant extracts to inhibit B. anthracis growth. Methods: Solvent extracts were prepared using various high antioxidant Australian fruits and herbs and investigated by disc diffusion assay for the ability to inhibit the growth of an environmental strain of B. anthracis. Their MIC values were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. The most potent extracts were analysed by non-targeted HPLC-QTOF mass spectroscopy (with screening against 3 compound databases) for the identification and characterisation of individual components in crude plant extracts. Results: Methanolic and aqueous extracts of several high antioxidant plant extract sdisplayed potent antibacterial activity in the disc diffusion assay against B. anthracis. The aqueous and methanolic extracts of lemon aspen, as well as the methanolic extracts of muntries, Illawarra plum and native tamarind were particularly potent growth inhibitors with MIC values<1000 µg/mL. Furthermore, all of these extracts were nontoxic in the Artemia fransiscana bioassay, with LC50 values substantially>1000 µg/mL. Non-biased phytochemical analysis of the lemon aspen aqueous and methanolic extracts putatively identified 85 compounds and highlighted several that may contribute to the ability of these extracts to inhibit the growth of B. anthracis. Conclusion: The low toxicity of several high antioxidant plant extracts and their potent inhibitory bioactivity against B. anthracis indicates their potential as medicinal agents in the treatment and prevention of anthrax. Lemon aspen is particularly worthy of further study.
Keywords: Anthrax; Antioxidant; Bacillus anthracis; lemon aspen; Muntries; Metabolomic profiling; Syzygium; Zoonotic